CONTENT AND FUNCTION OF THE QUR'AN - Pujiati Pujiati; Alwizar Alwizar (Jurnal Intelek Insan Cendikia, 2025)
The Qur'an is the word of God revealed by Allah SWT to the Prophet Muhammad Saw through the intermediary of the angel Gabriel. As the primary basis of Islamic teachings, the Qur'an contains the main content, which includes creed, worship, morals, law, and stories. The functions of the Qur'an are very diverse, including mau'idhah (teaching and warning), syifa' (healing), Sudan (guidance), rahmah (mercy), furqan (distinguishing), and as a perfection of the previous books. These functions are important provisions for mankind to live a life full of blessings and happiness in this world and the hereafter. As a guide to life (huda), the Qur'an provides clear direction regarding a good and proper life. As a differentiator (furqan), the Qur'an is the primary reference in distinguishing between halal and haram and right and wrong. In addition, the Qur'an also functions as a source of inspiration for science, a medium for purifying the soul (tazkiyah) through the practice of its verses, and a healer (stiff) for physical and spiritual health. These functions make the Qur'an a universal and relevant guide to life throughout the ages.